Dynamics and internal structure of a rock glacier: Inferring relationships from the combined use of differential synthetic aperture radar interferometry, electrical resistivity tomography and ground-penetrating radar - Buchelt, Sebastian; Kunz, Julius; Wiegand, Tim; Kneisel, Christof (Earth surface processes and landforms, 2024)
Rock glaciers are characteristic landforms in alpine environments originating from the movement of permanently frozen ground. Hereby, rock glacier velocity (RGV) is an important parameter for understanding the effects of climate change on mountain permafrost. Although understanding of rock glacier dynamics has increased during the last decades, linking small-scale surface kinematics to sub-surface properties and heterogeneities remains a challenge. To address this gap, we conducted geophysical surveys (electrical resistivity tomography [ERT] and ground-penetrating radar [GPR]) along two profile lines of 450 and 950 m in length on a rock glacier in the Central Swiss Alps. Additionally, RGV was derived from Sentinel-1 differential synthetic aperture radar interferometry (DInSAR) to quantify annual east-west displacement and elevation change as well as seasonal acceleration during the snow-free summer months with a ground sampling distance of 5 m. Our results show that movement angle and seasonality are highly associated with different patterns in sub-surface structure. These different movement patterns are linked to subunits of different morphological origins. Thereby, we can upscale the geophysical results based on the DInSAR surface movement parameters and outline an area within the study site probably affected by ice of glacial origin. Hence, DInSAR movement angle and seasonality can help to bring local sub-surface information derived from time-consuming geophysical investigations into the spatial domain. In this way, a better understanding of the current morphodynamics as well as the past and future evolution of the landform can be reached. Applying the approach to other sites with available geophysical investigations could enhance our knowledge about systematic links between surface kinematics and the internal structure of rock glaciers and other ice-rich glacial and peri-glacial landforms, as well as their response to a warming climate.
Online veröffentlicht: 29. September 2024
Gesehen am 14.10.2025